2018
DOI: 10.1109/ted.2018.2838439
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Geometry, 2-A Forward Current Ga2O3 Schottky Rectifiers on Bulk Ga2O3 Substrates

Abstract: Large area (up to 0.2 cm 2) Ga 2 O 3 rectifiers without edge termination were fabricated on a Si-doped n-Ga 2 O 3 drift layer grown by halide vapor phase epitaxy on a Sn-doped n + Ga 2 O 3 (001) substrate. A forward current of 2.2 A was achieved in single-sweep voltage mode, a record for Ga 2 O 3 rectifiers. The on-state resistance was 0.26 • cm 2 for these largest diodes, decreasing to 5.9 × 10-4 • cm 2 for 40 × 40 μm 2 devices. The temperature dependence (25°C-125°C) of forward current density was used to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 43 publications
(51 reference statements)
0
29
1
Order By: Relevance
“…The breakdown voltage (BV), defined as the voltage where reverse current (IR) reaches to 10 -5 A, shows a BV of -261 V for the device size of 1600×1600 µm 2 and increases to a BV of -427 V for the device size of 500 µm in diameter. The breakdown voltages in this work are higher than those in the previously published report [20]. The leakage current of the four Ga2O3 SBDs with large device size exhibits a relatively low current of IR~1.0×10 -10 A, corresponding to a current density of JR~1.0×10 -8 A/cm 2 , up to a reverse bias of VR=-50 V. It then monotonically increases until reaching the breakdown voltage.…”
Section: Device Characterization and Measurement Resultscontrasting
confidence: 50%
See 1 more Smart Citation
“…The breakdown voltage (BV), defined as the voltage where reverse current (IR) reaches to 10 -5 A, shows a BV of -261 V for the device size of 1600×1600 µm 2 and increases to a BV of -427 V for the device size of 500 µm in diameter. The breakdown voltages in this work are higher than those in the previously published report [20]. The leakage current of the four Ga2O3 SBDs with large device size exhibits a relatively low current of IR~1.0×10 -10 A, corresponding to a current density of JR~1.0×10 -8 A/cm 2 , up to a reverse bias of VR=-50 V. It then monotonically increases until reaching the breakdown voltage.…”
Section: Device Characterization and Measurement Resultscontrasting
confidence: 50%
“…Therefore, several high-power IEEE POWER ELECTRONICS REGULAR PAPER/LETTER/CORRESPONDENCE applications need large-size devices to produce high forward current while sustaining high breakdown voltage. Until now, only a limited number of studies on large-size Ga2O3 SBDs (> 1×10 -2 cm -3 ) have been conducted and Yang et al have reported a high forward current density of 36.7 A/cm 2 at 2.4 V for the device size of 6×10 -2 cm 2 [20]- [22]. The device performance has been hindered by a high concentration of defects in the active region, resulting in high leakage current.…”
mentioning
confidence: 99%
“…Field-plated, edge-terminated (FPET) vertical Schottky diodes were fabricated on a 20-μm thick Si-doped n-type Ga 2 O 3 drift layer grown on a 650-μm thick β-Ga 2 O 3 substrate using halide vapor phase epitaxy (HVPE). [23][24][25][26] The epi layer growth for Ga2O3 is still developing, and the breakdown voltage of the vertical diode is heavily relating to the number of defects within the drift region. Besides, the breakdown would still occur on the edges of these device contacts.…”
Section: Fabrication and Characterization Of High-reverse Voltage Ga 2 O 3 Schottky Rectifiersmentioning
confidence: 99%
“…By taking into account the estimated dielectric breakdown strength of 8 MV/cm, the calculated BFM of 3214 is outperforming more established semiconductors such as SiC or GaN [2]. Current research activities using β-Ga 2 O 3 are preferentially focusing on the development of Schottky barrier diodes (SBD) [3][4][5] and metal oxide semiconductor field-effect transistors (MOSFETs) [6][7][8][9][10][11] which have already demonstrated the high potential for high voltage applications reaching a peak field strength as high as 5.1 MV/cm in SBDs [12] and an average breakdown strength of 3.8-3.9 MV/cm in MOSFETs [13,14]. However, investigations on the switching performance and the dynamic properties of such devices have been rarely reported up to now.…”
mentioning
confidence: 99%